Transfer matrix method for dynamics modeling and independent modal space vibration control design of linear hybrid multibody system. (1st May 2018) - Rong, Bao; Rui, Xiaoting; Lu, Kun; Tao, Ling; Wang, Guoping; Ni, Xiaojun
Highlights: Transfer matrix method is studied for linear hybrid multibody system dynamics. A novel body dynamics equation, and augmented operator and eigenvector are given. A robust independent modal space-fuzzy control is presented for vibration control. Low memory requirement and high computational efficiency are realized. Abstract: In this paper, an efficient method of dynamics modeling and vibration control design of a linear hybrid multibody system (MS) is studied based on the transfer matrix method. The natural vibration characteristics of a linear hybrid MS are solved by using low-order transfer equations. Then, by constructing the brand-new body dynamics equation, augmented operator and augmented eigenvector, the orthogonality of augmented eigenvector of a linear hybrid MS is satisfied, and its state space model expressed in each independent model space is obtained easily. According to this dynamics model, a robust independent modal space-fuzzy controller is designed for vibration control of a general MS, and the genetic optimization of some critical control parameters of fuzzy tuners is also presented. Two illustrative examples are performed, which results show that this method is computationally efficient and with perfect control performance.